Design and Build an Application for Introduction to Endemic Indonesian Flora and Fauna Based on Virtual Reality - Aditiya Riyadhi; Ayung Candra Padmasari; Maya Purnama Sari (Universitas Pendidikan Indonesia (UPI), 2023)
Virtual Reality is a technology used in today's application development. Virtual Reality allows users to fully engage in a 3D visual environment and perform various activities. Indonesia has approximately 515 species that are threatened with extinction based on data on the IUCN website. The purpose of this research is to introduce rare biodiversity in Indonesia through a Virtual Reality-based application to reduce extinction rates. In the process of making applications, the authors use the SDLC (Software Development Life Cycle) Waterfall model, which is a software development model with organized and structured stages. SDLC Waterfall stages include needs analysis, planning or design, implementation, and testing, including 3D creation and integration with Unity3D. Testing is applied to the black box testing method. From the trials conducted, this application can run smoothly on computers and laptops with minimal specifications. The results of testing the application involving several respondents with an average percentage value of 87.67% are feasible and effective in making this application an educative media. This application is expected to increase public awareness about Indonesia's natural wealth as well as become an interesting and innovative educational tool.